Pengaruh Servicescape terhadap Kepuasan Konsumen pada Cafe Aceh Corner Medan - Intan Muliana; Arief Hadian (Medan Resource Center, 2021)
This study aims to determine and analyze the influence of servicescape on customer satisfaction at Café Aceh Corner Medan. The type of research conducted is descriptive quantitative research with an approach using a survey method that aims to determine the effect between two variables. The population in this study was 165 consumers, the number of samples to be taken in this study were 63 consumers. The sampling technique used was simple random sampling (simple). Data collection techniques can be done by interview (interview), questionnaire (questionnaire), observation (observation), and a combination of the three. The data analysis technique used is simple linear regression analysis. The result of the research is that the magnitude of the relationship between Servicescape and Consumer Satisfaction at Café Aceh Corner is 12.3%. This means that the Consumer Satisfaction of Café Aceh Corner is influenced by Servicescape by 12.3%. The value of the coefficient of constant (a) is 8793. This means that if the Servicescape value is equal to zero, then the amount of Customer Satisfaction is 8,793. The value of the regression coefficient (b) is 0.306 which indicates a change in the dependent variable based on the independent variable. tcount = 4.022. Because the calculated value (4.022) > ttable (1.658), in this case Ha is accepted and Ho is rejected. So it can be concluded that Servicescape has a significant effect on Consumer Satisfaction at Café Aceh Corner.